A new species of deropristid trematode from the sterlet Acipenser ruthenus (Actinopterygii: Acipenseridae) and revision of superfamily affiliation of the family Deropristidae. Issue 2 (21st March 2020) - Sokolov, Sergey; Voropaeva, Ekaterina; Atopkin, Dmitry
Abstract: A new species, Skrjabinopsolus nudidorsalis sp. nov. is described from the sterlet Acipenser ruthenus, caught in the River Volga basin (Russia). This species differs from previously described congeners by the absence of vitelline follicles on the dorsal side of the body. The complete 18S rRNA and partial 28S rRNA gene sequences obtained for S. nudidorsalis are the first molecular data for the family Deropristidae. The results of phylogenetic analysis indicate that Deropristidae is sister to the Monorchiidae + Lissorchiidae group. The results of the phylogenetic study contradict the current taxonomic hypothesis that Deropristidae belongs to the superfamily Lepocreadioidea and allow inclusion of this family in Monorchioidea. The morphological similarity of deropristids to other monorchioids is recognizable from the presence of a bipartite internal seminal vesicle, spinous cirrus and a voluminous, armed metraterm.